The effect of marketing orientation on marketing competence and it’s implications on sales performance - R Susanto Hendiarto; Zaenal Musthafa (Enrichment : Journal of Management, 2023)
The current problem is that sales are still far from expectations, while the competencies that must be possessed are also still of concern. This is allegedly because the marketing orientation has not been built according to the business platform, so that many business targets are not achieved. This study aims to determine the effect of marketing orientation on marketing competence and its implications for sales performance, examining case studies on businesses assisted by Kadin Jabar in Bandung. The research method applied was in the form of an analytical descriptive survey method, while the sample used was 39 respondents. The variables studied from each respondent are marketing orientation, marketing competence, and sales performance. The type of data collected is primary data. The results of the study show that marketing orientation has a significant effect on marketing competence. Marketing competence has a significant effect on sales performance. The implication is that the marketing orientation of MSMEs as a stimulus must be immediately decided by management to create competent human resources, especially in the field of marketing, in order to produce performance in the field of sales according to target achievements. The object of this research is that the responden sample used is still limited to the West Java Kadin assisted businesses in Bandung, therefore it is necessary to carry out further research based on a more varied sampling with a longer duration, so that results can be generalized.